Can Inoculation With the Bacterial Biostimulant Enterobacter sp. Strain 15S Be an Approach for the Smarter P Fertilization of Maize and Cucumber Plants? - Alzate Zuluaga, Mónica Yorlady; Martinez de Oliveira, André Luiz; Valentinuzzi, Fabio; Tiziani, Raphael; Pii, Youry; Mimmo, Tanja; Cesco, Stefano (Frontiers in Plant Science, 2021)
Phosphorus (P) is an essential nutrient for plants and the use of plant growth-promoting bacteria may improve plant development and enhance nutrient availability, thus providing a promising alternative or supplement to chemical fertilizers. This study aimed at evaluating the effectiveness of Enterobacter sp. strain 15S in improving the growth and P acquisition of maize (monocot) and cucumber (dicot) plants under P-deficient hydroponic conditions, either by itself or by solubilizing an external source of inorganic phosphate (Ca3(PO4)2). The inoculation with Enterobacter 15S elicited different effects on the root architecture and biomass of cucumber and maize depending on the P-supply. Under sufficient P, the bacterium induced a positive effect on the whole root system architecture of both plants. However, under P deficiency, the bacterium in combination with Ca3(PO4)2 induced a more remarkable effect on cucumber, while the bacterium alone was better in improving the root system of maize compared to non-inoculated plants. In P-deficient plants, bacterial inoculation also led to a chlorophyll content (SPAD index) like P-sufficient plants (p < 0.05). Regarding P nutrition, the ionomic analysis indicated that inoculation with Enterobacter 15S increased the allocation of P in roots (+31%) and shoots (+53%) of cucumber plants grown in P-free nutrient solution supplemented with the external insoluble phosphate, whereas maize plants inoculated with the bacterium alone showed a higher content of P only in roots (36%) but not in shoots. Furthermore, in P-deficient cucumber plants all Pi transporter genes (CsPT1.3, CsPT1.4, CsPT1.9 and Cucsa383630.1) were up-regulated with bacterium inoculation, whereas in P-deficient maize plants the expression of ZmPT1 and ZmPT5 was down-regulated by the bacterial inoculation. Taken together, these results suggest that in the interaction with P-deficient cucumber plants, Enterobacter strain 15S might have solubilized the Ca3(PO4)2 in order to help plants to overcome P deficiency, while the association of maize plants with the bacterium might have triggered a different mechanism affecting plant metabolism. Thus, the mechanisms by which Enterobacter 15S improves plant growth and P nutrition is dependent on crop and nutrient status.